Developments in the ‘LNG to Power’ market and the growing importance of floating facilities - Wyllie, M (Oxford Institute for Energy Studies, 2021)
Land-based LNG import terminals were introduced in the 1960s to import LNG from the first liquefaction plants in Algeria and the USA and dispatch gas into national distribution grids. Since then, some 150 LNG import terminals have been built around the world. In the last 20 years there has been a growth in the number of floating LNG import terminals facilities which have become popular since they can generally be deployed more quickly and at a lower cost than onshore facilities.